2000
DOI: 10.1177/039139880002300109
|View full text |Cite
|
Sign up to set email alerts
|

Photopheresis in Cutaneous T-Cell Lymphoma: Five-Year Experience

Abstract: In our experience ECP achieved favourable clinical responses in 73% of patients, in monotherapy or in combination with IFN-alpha, without significant side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Reported overall response rates vary between 31% and 86% (see Table 1). 1,55–69 CR rates, however, are much lower, ranging from 0 to 33%. Different response rates may relate to differences in entry criteria such as the presence of a peripheral blood T‐cell clone, prior or adjuvant therapy, interval between diagnosis and treatment, ECP protocol, duration of ECP and definition of treatment response.…”
Section: Extracorporeal Photochemotherapy For Cutaneous T‐cell Lymphomamentioning
confidence: 95%
“…Reported overall response rates vary between 31% and 86% (see Table 1). 1,55–69 CR rates, however, are much lower, ranging from 0 to 33%. Different response rates may relate to differences in entry criteria such as the presence of a peripheral blood T‐cell clone, prior or adjuvant therapy, interval between diagnosis and treatment, ECP protocol, duration of ECP and definition of treatment response.…”
Section: Extracorporeal Photochemotherapy For Cutaneous T‐cell Lymphomamentioning
confidence: 95%
“…Based on these criteria, we identified 28 studies, in the majority of cases retrospective and based on single institution series. A total of 407 patients reported as erythrodermic were included (Table ) …”
Section: Extracorporeal Photopheresis For the Treatment Of Erythrodermentioning
confidence: 99%
“…Those studies in which SS has been clearly defined and an OR defined as at least 50% clearing are shown in Table I. 84,90,151,[153][154][155][156][157][158] However, there are notable publications where response in patients with SS to ECP (given as 2 consecutive days monthly) is defined only as at least 25% clearing. Not surprisingly, the RR is higher in these cases: de Misa et al 158 reported on 60% response in the skin in 10 patients with SS (defined as T 4 1 [5% peripheral blood SC 1 clonal involvement) and Evans et al 159 noted a response in skin in 57% of patients with SS (defined stringently as T 4 , $ 10% peripheral blood SC, and clonality TCR gene rearrangement).…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%